Kelayakan Buku Pop-Up Sebagai Alternatif Media Pendidikan Kesehatan Reproduksi (The Feasibility of Pop-Up Book as Alternative Reproduction Health Education Media) - Rika Agustin; Erdi Istiaji; Dewi Rokhmah (Pustaka Kesehatan, 2014)
Children are always risky exposed to pornography of mass media every day. Children sexualviolence is growing too, especially the number of case of sexual violence always ranks topthan other case of violence in Jember regency. The existence of awareness of reproductionhealth education grants in children early is one way to cope with case of sexual violence.Researcher made pop-up book as an alternative reproduction health education mediadevoted to elementary school students between grade 3-4. This research aimed to find outthe feasibility of the pop-up book media from presenting physical appearance and suitabilityof the material. This research was applied in descriptive method with qualitative approach.Data was collected by in-depth interview, triangulation, and documentations. The resultshowed that overall the colors used were in accordance with the children for colorfull,typography used have qualified legibility and readability, lllustrations used was in accordancewith the explanation was given and so attractive for children, and the layout of were used as awhole had met the principle of unity. While the content of each theme was in compliance withthe children, but there had to be improvement of the writing, the use of words, and thecontent.Keywords: Pop-Up, Reproduction Health, Children